KONSELING INDIVIDU TEKNIK CLIENT CENTERED DALAM MENINGKATKAN REGULASI EMOSI PADA REMAJA FATHERLESS - Febrianti, Nadia riski; Wiantina, Nur Azmi; Muttaqin, Muhammad Fauzan (IKIP Siliwangi, 2025)
This study aims to examine the effectiveness of individual counseling using the client-centered technique in improving emotional regulation among fatherless adolescents. Adolescence is a critical stage marked by emotional instability, especially for those who grow up without a father figure. Fatherlessness can trigger emotional issues such as anxiety, anger, and difficulties in social interaction. This research employed a qualitative approach with a case study method involving a ninth-grade student at SMPN 18 Tangerang who experienced fatherlessness due to parental divorce. Data were collected through observation, interviews, and documentation. Thematic analysis was used to identify key patterns and emotional themes from the subject’s experiences. The findings indicate that the client-centered technique supported the counselee in recognizing, expressing, and managing emotions more adaptively. After four counseling sessions, the subject demonstrated improved emotional regulation, such as better emotional expression, use of positive coping strategies, and increased learning motivation. This humanistic-based counseling approach proved effective by providing a safe and non-judgmental space, allowing the counselee to explore self-awareness and develop healthier emotional responses. Thus, client-centered individual counseling can serve as a viable intervention strategy to support the psychological well-being of fatherless adolescents.